Cerebrotendinous xanthomatosis - Soedarmadji, Soedarmadji (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
A case of cerebrotendinous xanthomatosis in an Indonesian male, 25 years of age, is reported. The diagnosis was based on clinical features, laboratory and histopathologic examinations, without measurement of cholestanal concentration either in the plasma or in the xanthoma.Key Words: xanthoma - normolipidemia lipoidosis - cataracta juvenilis - neurologic disturbÂ